Nilai-Nilai Pendidikan Akhlak Dalam Kitab Risalatul Muawanah Karya Sayyid Syarif Abdullah Bin Alwi Bin Muhammad Al-Haddad (Bab Menjaga Adab-adab Tingkah Laku) - Zaidatun Ni’mah Julifiyana; Ngarifin Shidiq; Nur Farida (JURNAL ILMIAH NUSANTARA, 2025)
. In the midst of global challenges such as moral degradation, individualism, and the rise of hate speech, strengthening ethical and moral values has become an urgent need in the field of education. Islam, as a comprehensive religion, emphasizes the importance of morality through teachings derived from the Qur’an, Hadith, and classical scholarly works. This article aims to examine the moral educational values contained in the chapter "Maintaining Proper Conduct and Manners" (Bab Menjaga Adab-adab Tingkah Laku) from the book Risalatul Mu‘awanah by Sayyid Abdullah bin Alwi bin Muhammad Al-Haddad, and to assess its relevance to contemporary education. This study employs library research using a descriptive qualitative approach and content analysis. The findings reveal that this chapter contains essential moral values such as guarding one’s speech from gossip, speaking politely, avoiding careless oaths, and demonstrating proper behavior in dressing, eating, sleeping, and social interaction. These values emphasize the importance of morality, politeness, and social harmony, and remain highly relevant to character education today, especially amid the current moral crisis and growing individualism. The book Risalatul Mu‘awanah excels in delivering moral teachings in a concise, clear, and systematic manner. Although written in classical Arabic and not addressing modern issues explicitly, its teachings are still contextual and applicable. Therefore, its content deserves integration into both formal and non-formal education systems as a reference for building strong Islamic character.